The unspoken name - Larkwood, A. K. ([Serpent Gates, 2020)
"What if you knew how and when you will die? Csorwe does. She will climb the mountain, enter the Shrine of the Unspoken, and gain the most honored title: sacrifice. On the day of her foretold death, however, a powerful mage offers her a new fate. Csorwe leaves her home, her destiny, and her god to become the wizard's loyal sword-hand -- stealing, spying, and killing to help him reclaim his seat of power in the homeland from which he was exiled. But Csorwe and the wizard will soon learn - gods remember, and if you live long enough, all debts come due"--